Modelagem molecular de derivados pirimidínicos e estudos de docking nas enzimas ciclooxigenase 1 e ciclooxigenase 2 - Armelin, Paulo Roberto Gabbai (2010)
In this research molecular docking was used to study enzime-ligand complexes of Cyclooxygenase 1 (COX-1) and Cyclooxygenase 2 (COX-2) with pyrimidine derivatives, aiming at understanding the possible mechanisms of action of these compounds and, thus, suggest modifications that could increase their specificity. The chosen ligands were a series of 25 substituted pyrimidines with known activity. The three-dimensional structures of these compounds were obtained by molecular modeling and that of the enzymes from the PDB and PDBSum under the codes 2OYE and 1CX2 for COX-1 and COX-2 respectively. The binding sites chosen for the docking studies were 20 Å around the crystallographic ligands IM8-700 (2OYE) and SC-558 (1CX2). In the COX-1 formed complexes the SO2Me moiety is positioned in such a way as to form hydrogen bonds with Ile517 and Phe518. The benzo[b]thiophen-2-ylmethyl-[2-(4-methanesulfonylphenyl)-6-trifluoromethylpyrimidin-4- yl]amine formed the most favorable complex with COX-1. In COX-2, the enzyme-ligand interaction pattern shows the SO2Me group in the side pocket, forming hydrogen bonds with His90 and Arg513 and the different substituent groups of the pyrimidine ring form hydrogen bonds with Arg120 and Tyr355. The presence of a small lipophilic pocket in COX-2 and the docking results suggest that the ligands 2, 15, 17, 22 and 23 may have their activity enhanced by the addition of a hydrophobic group on the phenyl or thiophenyl rings so this group can interact within this pocket. In both cases the mechanism of inhibition is probably competitive. As the search for new anti-inflammatory drugs must deal with a subtle balance of COX-2 and COX-1 inhibitions, the ligands 2 and 22 that showed better results for COX-2 rather than for COX-1 would be the most promising ones and therefore, those that should be tested in vivo.